A new taxonomy of neuroprotective agents for stroke appropriate for the reperfusion era - Bahr-Hosseini, Mersedeh; Saver, Jeffrey L. (Frontiers in Neurology, 2025)
The advent of the era of highly effective reperfusion therapy for acute ischemic stroke has reawakened interest in neuroprotective treatments as they are far more likely to be efficacious as synergistic complements to reperfusion rather than standalone interventions. However, testing neuroprotective agents combined with reperfusion mandates not only renewed conduct of trials but also a fundamental reconceptualization of the subclasses of neuroprotection therapies. We propose a new taxonomy of neuroprotective treatment agents appropriate for the reperfusion era that recognizes six broad classes of agents, each targeting a distinct process and time epoch of injury: (1) Bridging neuroprotectives slow infarct expansion in the pre-reperfusion period, (2) Blood–brain barrier stabilizers restore the integrity of BBB before and early after reperfusion, (3) Microcirculation lumen preservers protect arteriolar and capillary endothelial cell integrity deterring the no-reflow phenomenon, (4) Reperfusion injury preventors block inflammatory, oxidative, and other processes that start immediately after reperfusion, (5) Edema reducers avert cerebral swelling and secondary injury due to brain tissue compression and herniation, and (6) Delayed neuroprotectives mitigate injury due to apoptosis and mitochondrial dysfunction in the late post-reperfusion period. This approach also broadly distinguishes neuroprotection from other major treatment strategies, including recanalization, collateral enhancement, and neurorepair. By focusing on broad physiologic targets of action rather than granular molecular mechanisms, this six-fold classification of neuroprotection can inform the design of preclinical studies and human clinical trials, including imaging biomarker endpoint selection and treatment timing. This updated taxonomy may accelerate the translation of cerebroprotective agents from bench to bedside.